2019
DOI: 10.1111/jgh.14565
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mucosal healing during induction therapy in patients with acute moderate‐to‐severe ulcerative colitis

Abstract: Background and Aim The treat‐to‐target strategy has emerged in ulcerative colitis management. Mucosal healing is the best target, albeit not in induction therapy of acute diseases as clinical conditions vary over a short duration. To determine the targets during induction therapy for acute ulcerative colitis, we identified markers to predict mucosal healing at 3 and 12 months of initiating the induction therapy. Methods This single‐center prospective observational study enrolling 61 adult patients hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The treatment regimen of corticosteroids consisted of (a) methylprednisolone weekly dose intravenous bolus‐administered vs conventional orally taken daily (both arms 12‐week tapering regimen starting from 450 mg/wk) and (b) next‐generation budesonide‐MMX orally (8‐week regimen of 9 mg stable dose). In the third study, the specification of type and dose of corticosteroids was not disclosed 9,27,29 . Anti‐TNFα agents used included infliximab only, 9,28 either infliximab or adalimumab (n = 104 and n = 10, respectively), 14 and unspecified anti‐TNFα agents 29 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment regimen of corticosteroids consisted of (a) methylprednisolone weekly dose intravenous bolus‐administered vs conventional orally taken daily (both arms 12‐week tapering regimen starting from 450 mg/wk) and (b) next‐generation budesonide‐MMX orally (8‐week regimen of 9 mg stable dose). In the third study, the specification of type and dose of corticosteroids was not disclosed 9,27,29 . Anti‐TNFα agents used included infliximab only, 9,28 either infliximab or adalimumab (n = 104 and n = 10, respectively), 14 and unspecified anti‐TNFα agents 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Agreement between reviewers for trial eligibility was good (κ statistic 0.74). We successfully contacted 11 authors: from 8 studies individual patient data were shared, 9,10,13,14,24‐27 from three studies aggregated data were provided 28‐30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fecal calprotectin seems to have a predictive value in ASUC, but it was not routinely measured in our centers 6,34 . Moreover, we focused on colectomy after ASUC, but, nowadays, it would be interesting to have predictors of others issues such as mucosal healing, or success of specific biologics or small molecules 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been found that the 10‐year cumulative risk of colectomy is 10–15% 5 . To avoid these complications, colonic mucosal healing has gained progressive importance in the management of UC patients 6–8 …”
Section: Introductionmentioning
confidence: 99%